Species of Paraclius Loew (Diptera: Dolichopodidae) with bi-lamellate antennal stylus: new combination, new synonym, and two new species - Soares, Matheus M. M.; Capellari, Renato S.; Ale-Rocha, Rosaly (Zootaxa, 2023)
The species of Paraclius Loew with bi-lamellate arista-like stylus are revised and P. americanus (Schiner, 1868) comb. nov. is transferred from Tachytrechus Haliday and regarded as the senior synonym of P. diplacocerus Capellari, 2013 syn. nov. In addition, two new species with similar antennal morphology are described and illustrated from Brazil: P. bilamellatus sp. nov. (States of Espírito Santo and Goiás) and P. vulcanoae sp. nov. (State of São Paulo). A distribution map and a key to the males of known species of Paraclius with bi-lamellate arista-stylus are provided.